Comparison of color match of metal-ceramic tooth crowns fabricated by laboratory technicians with and without academic education - Reaz Khodadadi; Rasool Monirifar; Navid Asgari; Mohammad Baharvandi (Isfahan University of Medical Sciences, 2011)
Introduction: A common procedure in esthetic dentistry is fabrication of metal-ceramic veneer crowns that have proper color match with the patient's teeth. The aim of this study was to compare color reproduction of the selected color by dental practitioners in dental laboratories by technicians with and without academic education. Materials and methods: In this in vitro study a maxillary incisor from a dental model was prepared for a metal-ceramic veneer crown. After impression taking and making a standard framework, 36 impressions were taken for 36 laboratories and two standard metal frameworks were fabricated on each die. Two frameworks were sent to each laboratory. A3 porcelain was requested to be placed on the standard frameworks and glazed. Each specimen was tested with Shadepilot equipment. a*, b* and L* color indexes and DE were determined at incisal, middle and cervical areas of each crown. T-test and linear regression were used for data analysis (α=0.05).Results: Means and standard deviations of DE of samples in the group without academic education at incisal, middle, and cervical areas were 3.56±1.93, 2.54±2.40, and in 3.0±1.16, respectively; corresponding values in the group with academic education were 5.6±3.19, 2.11±1.02, and 21.18±0.72, respectively. T-test showed significant differences in DE of incisal areas between the two groups (P=0.003), with no significant differences in other areas.Conclusion: In this study, there was a significant relationship between job experience and color match accuracy in the incisal region, indicating that technicians with more job, but with no academic education, exhibit more accuracy in reconstructing incisal edge color of metal-ceramic veneer crowns. Key word: Tooth crown, Color, Spectrophotometry.